Uma análise sobre sistemas de informação governamentais para educação profissional e tecnológica: na busca pela qualificação dos dados declarados - Machado, Franciele de Lima (2018)
Professional and Technological Education (EPT) has gained prominence in recent years, mainly due to investment and improvement in public policies and programs that have increased the number of vacancies and the number of technical and professional education institutions in Brazil. According to this context, the Information Systems (SI) Educacenso, National Information System of Professional and Technological Education (SISTEC) and Nilo Peçanha Platform (PNP) stand out as data acquisition tools that support the planning, execution and control of actions related to EPT. Based on the identification of disconformities and insertion, operation and dissemination of results difficulties on these SI, in view of their relevance for public management, it was noticed the need to study them, in order to list points that need to be improved, thus contributing to the qualification and reliability of the declared data. The present work is described as an applied exploratory research, of qualitative nature, case study type, produced through the application of semi-structured interviews carried out with people responsible for the supply of the SI surveyed, in educational institutions belonging to the Private Network and the Municipal, State and Federal Public Networks from the municipality of Santa Maria, Rio Grande do Sul. In a general way, this research aimed to analyze each SI, understanding its purposes and functionalities, identifying its main difficulties, from the point of view of the users responsible for filling each one of them. It was verified that the systems do not work as planned, that they have a series of instabilities and problems in their mechanisms of training, collection, storage, control and data analysis, besides the fact that their users do not know the importance of their work and do not understand what each system is and what it is for. The lack of integration, communication and fluidity of information between sectors and government agencies seems to be a great obstacle to the construction of a global vision, which would facilitate the proposition of more assertive and efficient strategies and measures regarding national education.